Biophysical Economics as a New Economic Paradigm. Issue 15 (10th December 2019) - Yan, Jun; Feng, Lianyong; Steblyanskaya, Alina; Kleiner, George; Rybachuk, Maxim
ABSTRACT: Global civilization is experiencing social and economic turmoil. Human are experiencing deterioration of environment and uncontrollable declines in GDP. Traditional economic theory has been continuously advancing yet seems unable to predict these crises or provide adequate public policies to address them. A biophysical version of economic theory uses mass and energy flows as well as environmental constraints to describe the delivery of goods and services. Ongoing development in biophysical economic theory may provide some new guidance. In this review paper, Authors analyze the progression of historical economic arguments, explore their assumptions and their development and compare them to the currently developing biophysical economics framework which, instead of focusing on investment, debt, and growth, focuses on sustainable energy and mass flows to deliver goods and services to civilization.